Peningkatan sadar lingkungan melalui penghematan sampah plastik - Anindyntha, Firdha Aksari; Susilowati, Dwi; Sulistyono, Setyo Wahyu (University of Islam Malang, 2021)
Plastic waste is difficult to decompose, so it causes environmental problems. The amount of environmental pollution by plastic waste in Indonesia is due to the lack of balance between the volume of waste and its handling efforts. The increasing volume of plastic waste has an impact on the severity of waste processing in Integrated Waste Disposal Sites. The community service team in collaboration with Mulyoagung Village Head held a community service program to change people's habits from passive about waste to active through waste saving education. There are three activities in this program, namely educate the public to reduce household waste especially plastic, carry out a campaign to save plastic waste by making and installing posters or billboards in strategic places, and encourage the Mulyoagung Village apparatus to initiate the use of tumbler. The result of this activity is the high participation of the community as seen from attendance of participants and enthusiasm of participants to ask questions, installation of posters and billboards, also used of tumblers to village office every day. To make this activity can be continuity and sustainable, the community service team will do community service program in the same place with the theme of environmental problems.